DESKRIPSI KONFORMITAS TEMAN SEBAYA DAN PERILAKU KONSUMTIF TERHADAP PRODUK APPLE SISWA DI SMA NEGERI 5 SOPPENG - Azzahra, Ummah; saman, Abdul; Fitriana; Maslina (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the level of peer conformity and the level of consumptive behavior towards Apple products among students. This research used a quantitative approach with descriptive methods. Data were collected using a Likert scale questionnaire adapted from Baron & Byrne's theory for conformity and Lina & Rosyid's theory for consumptive behavior. Data analysis used descriptive statistics to calculate frequencies and percentages. The results showed that the level of peer conformity among students was in the high category (43.42%), and the level of consumptive behavior towards Apple products was in the very high category (53.95%). The conclusion of this study is that the majority of students have a strong tendency to conform to their peer groups and exhibit excessive consumption patterns of Apple products, driven by aspects of impulsive buying, wasteful buying, and non-rational buying.